Applying telecommunications methodology to road safety for rear-end collision avoidance. (January 2015) - Benedetto, Francesco; Calvi, Alessandro; D'Amico, Fabrizio; Giunta, Gaetano
Highlights: One of the crucial priorities for the world society is road safety improvement. We apply telecommunications methods to road safety for avoiding rear-end collisions. Our test only need a cheap radio transmitter/receiver, mounted on each vehicle. The detection probability of the method is evaluated versus several driving conditions. Our test is characterized by higher detections in correspondence of small distances. Abstract: This work aims at applying telecommunications methodologies to road safety for preventing rear-end collisions. This contribution can be considered as a pilot study to verify and assess the reliability of a new model and procedure for collision warning system based on low-cost inter-vehicular communications (only a cheap radio transmitter/receiver mounted on each vehicle is needed), where Global Positioning Systems (GPS) and other distance vector-based networks are not employed. A signal processing method, namely the binomial test, aimed at detecting approaching sources in infrastructure-less vehicular communications is here proposed and discussed. The detection probability of the method is evaluated versus several driving conditions, in terms of relative speeds and distances between vehicles. In addition, the Time To Collision ( TTC ), generally required before declaring a correct detection by existing collision systems implemented in recent vehicles, is evaluated for several driving scenarios characterized by different setting parameters. Our numerical results confirm the validity of such an approach in preventing rear-end collisions, allowing a fast detection of approaching sources.